Dopamine D2/D3 imbalance during migraine attack and allodynia in vivo. (25th April 2017) - DaSilva, Alexandre F.; Nascimento, Thiago D.; Jassar, Hassan; Heffernan, Joseph; Toback, Rebecca L.; Lucas, Sarah; DosSantos, Marcos F.; Bellile, Emily L.; Boonstra, Philip S.; Taylor, Jeremy M.G.; Casey, Kenneth L.; Koeppe, Robert A.; et al.
Abstract : Objective: To evaluate in vivo the dynamics of endogenous dopamine (DA) neurotransmission during migraine ictus with allodynia. Methods: We examined 8 episodic migraineurs and 8 healthy controls (HC) using PET with [ 11 C]raclopride. The uptake measure of [ 11 C]raclopride, nondisplaceable binding potential (BPND ), would increase when there was a reduction in endogenous DA release. The opposite is true for a decrease in [ 11 C]raclopride BPND . Patients were scanned twice: one PET session was during a spontaneous migraine ictus at rest, followed by a sustained thermal pain threshold (STPT) challenge on the trigeminal region, eliciting an allodynia experience; another was during interictal phase. Results: Striatal BPND of [ 11 C]raclopride in migraineurs did not differ from HC. We found a significant increase in [ 11 C]raclopride BPND in the striatum region of migraineurs during both headache attack and allodynia relative to interictal phase. However, when compared to the migraine attack at rest, migraineurs during the STPT challenge had a significant sudden reduction in [ 11 C]raclopride BPND in the insula. Such directional change was also observed in the caudate of HC relative to the interictal phase during challenge. Furthermore, ictal changes in [ 11 C]raclopride BPND in migraineurs at rest were positively correlated with the chronicity of migraine attacks, and negatively correlated with the frequency during challenge. Conclusions: Our findings demonstrate that there is an imbalanced uptake of [ 11 C]raclopride during the headache attack and ictal allodynia, which indicates reduction and fluctuation in ictal endogenous DA release in migraineurs. Moreover, the longer the history and recurrence of migraine attacks, the lower the ictal endogenous DA release.